Role of Vitamin D in Premature Atherosclerosis in Adolescents Type 1 Diabetes through Transforming Growth Factor-β1, Interferon-γ, Interleukin-10, and Interleukin-17 - Cahyono, Haryudi Aji; Barlianto, Wisnu; Handayani, Dian; Kalim, Handono (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Cardiovascular disease (CVD) is one the cause of mortality in patients with type 1 diabetes (T1D). The development of CVD is mainly triggered by atherosclerosis, which is associated with the inflammatory process. AIM: The current study was aimed to investigate the association of Vitamin D level and premature atherosclerosis in adolescents with T1D, mainly through the regulation of various cytokines (interferon-γ [IFN-γ], IL-17, interleukin-10 [IL-10], and transforming growth factor-β1 [TGF-β1]). METHODS: This study was designed as a cross-sectional study involving 40 T1D and 40 healthy control who came to the outpatient clinic, Saiful Anwar Hospital, Malang, Indonesia, within the study period (January 2019-July 2019). RESULTS: Our data demonstrated that the IFN-γ and IL-17 levels were significantly higher (p < 0.001), whereas the TGF-β1 and IL-10 levels were significantly lower (p < 0.001) in T1D group compared with control. Furthermore, T1D also has higher carotid intima-media thickness (cIMT) value and lower flow-mediated dilatation (FMD) value compared to the control group (p < 0.001). Level of 25(OH)D3 was strongly associated with reduced cIMT and elevated FMD (p < 0.005). The direct effect of 25(OH)D3 on cIMT and FMD was higher than the indirect effect of Vitamin D through TGF-β1, IL-10, IL-17, and IFN-γ. The cutoff value of 25(OH)D3 levels for the risk of atherosclerosis was 12.8 ng/dL (sensitivity 85.7% and specificity 86.7%). CONCLUSION: The level of Vitamin D in the T1D group was significantly lower than those in healthy children and Vitamin D deficiency substantially influences the formation of premature atherosclerosis.